The Composition of Anthropology
1 online resource (xi, 129 pages)
Keywords: "How do anthropologists write their texts? What is the nature of creativity in the discipline of anthropology? This book follows anthropologists into spaces where words, ideas and arguments take shape and explores the steps in a creative process. In a unique examination of how texts come to be composed, the editors bring together a distinguished group of anthropologists who offer valuable insight into their writing habits. These reflexive glimpses into personal creativity reveal not only the processes by which theory and ethnography come, in particular cases, to be represented on the page but also supply examples that students may follow or adapt."--Provided by publisher.